2020
DOI: 10.1371/journal.pone.0230937
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of superb microvascular imaging and contrast-enhanced ultrasonography in detection of intraplaque neovascularization: A meta-analysis

Abstract: This meta-analysis assesses the consistency of superb microvascular imaging (SMI) and contrast-enhanced ultrasonography (CEUS) in detecting intraplaque neovascularization (IPN). We searched PubMed, Web of Science, the Cochrane Library, and CBM databases. A meta-analysis was conducted using STATA version 15.1 software. We calculated the pooled Kappa index. Ten studies that met all of the inclusion criteria were included in this meta-analysis. A total of 608 carotid plaques were assessed through both SMI and CEU… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…29 The meta-analysis of this study showed that carotid IPN detected in SMI is highly correlated to which in CEUS, and substantial agreement with which in CEUS, similar to other reports. 30,31 Furthermore, our findings suggested that carotid IPN identified in SMI is highly correlated to the evaluation of pathology. Previous studies have indicated IPN highly associated with ischemic stroke in TIA patients, 32 our findings also demonstrated patients with IPN detected by SMI more likely to be exposed to stroke or TIA.…”
Section: Discussionmentioning
confidence: 57%
“…29 The meta-analysis of this study showed that carotid IPN detected in SMI is highly correlated to which in CEUS, and substantial agreement with which in CEUS, similar to other reports. 30,31 Furthermore, our findings suggested that carotid IPN identified in SMI is highly correlated to the evaluation of pathology. Previous studies have indicated IPN highly associated with ischemic stroke in TIA patients, 32 our findings also demonstrated patients with IPN detected by SMI more likely to be exposed to stroke or TIA.…”
Section: Discussionmentioning
confidence: 57%
“…Many patients with CAS often have no obvious clinical symptoms, while acute ischemic symptoms, such as sudden stroke and hemiplegia, are often caused by carotid plaques or thrombus on the surface of plaque, leading to intracranial arteriovenous ischemia. 6 Therefore, it is of great clinical significance to study the stability of carotid plaque for preventing serious complications.…”
Section: Introductionmentioning
confidence: 99%
“…SMI does not use contrast agents while CEUS uses adaptive principles to display low-velocity blood flow signals ( 6 ). Two recently published meta-analysis demonstrated that SMI and CEUS display excellent diagnostic value for detecting carotid IPN ( 7 , 8 ). However, the analysis could not draw conclusions regarding the accuracy of SMI since the sample sizes in the relevant studies were small ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%